With us, there's a future / Ain Syafiqa Shah Dahli and Anis Syamimi Mohammad - Shah Dahli, Ain Syafiqa; Mohammad, Anis Syamimi (Faculty of Information Management, 2014)
In this era, youth willingly to go to further study in order to make sure they get a better job in future. They will choose study field that they think can give them a good job like engineering, medical, law and more instead of choosing the field like language, farming and information management. But, they do not know that the field that they 'think' low class and cannot give them bright future has the most employments opportunities.